Quality assessment of osteoporosis clinical practice guidelines for physical activity and safe movement: an AGREE II appraisal. Issue 1 (December 2016) - Armstrong, James; Rodrigues, Isabel; Wasiuta, Tom; MacDermid, Joy
Abstract Summary Many osteoporosis clinical practice guidelines are published, and the extent to which physical activity and safe movement is addressed varies. To better inform clinical decision-making, a quality assessment and structured analysis of recommendations was undertaken. Guideline quality varied substantially, and improvement is necessary in physical activity and safe movement recommendations. Purpose The purpose of the present study is to survey available osteoporosis clinical practice guidelines (CPGs) containing physical activity and safe movement recommendations in order to assess the methodological quality with which they were developed. An analysis of the various physical activity and safe movement recommendations was conducted to determine variability between CPGs. Methods An online literature search revealed 19 CPGs meeting our inclusion criteria. Three independent scorers evaluated CPG quality using the Appraisal of Guidelines for Research and Evaluation version II (AGREE II) instrument. Two separate individuals used a standard table to extract relevant recommendations. Results Intra-reviewer AGREE II score agreement ranged from fair to good (intra-class correlation coefficient (ICC) = 0.34 to 0.65). The quality of the 19 included CPGs was variable (AGREE sub-scores: 14 to 100 %). CPGs scored higher in the "scope and purpose" and "clarity of presentation" domains. They scored the lowest in "applicability" and "editorial independence." Four CPGs were classified as high quality, ten average quality, and five low quality. Most CPGs recommended weight-bearing, muscle-strengthening, and resistance exercises. Information on exercise dosage, progression, and contraindications was often absent. Immobility and movements involving spinal flexion and/or torsion were discouraged. Conclusions There were several high-quality CPGs; however, variability in quality and lack of specific parameters for implementation necessitates caution and critical examination by readers. CPG development groups should pay special attention to the clinical applicability of their CPGs as well as fully disclosing conflicts of interest. CPGs were in general an agreement regarding safe physical activity and safe movement recommendations. However, recommendations were often vague and the more specific recommendations were inconsistent between CPGs.